(untitled) (Research, Society and Development, 2020)
Education has been undergoing major changes in teaching methodological issues, given that, the National Curriculum Parameters (or Parâmetros Curriculares Nacionais) present pedagogical proposals, it is up to school managers to enable the use of these resources to improve the quality of teaching. The contents applied to the discipline of Biology should not only remain centered on the methodology based on the transmission of information through the textbook. It is necessary that the teacher seeks strategies that will contribute to the knowledge of high school students, in the student’s continuous training. Thus, the present study aimed to investigate what are the difficulties encountered by Biology teachers in the development of new teaching methods, as well as to understand the reasons for not using them in the school’s daily life. The data collected for analysis of the study were obtained through a questionnaire carried out with Biology teachers from a Public School in the city of Manaus. A percentage of teachers stated that they do not apply new methods due to lack of time, others say that the use of books alone is still one of the main mediators of information, others pointed out that the use of new methods would complement the theoretical classes. The lack of these modalities directly implies the student’s learning and there are factors that contribute to the failure in the teaching-learning process. Therefore, it is necessary to discuss and reflect on these factors so that situations can be developed to adapt it to different teaching realities.